Pengembangan Bahan Ajar Menulis Cerita Fantasi Bermuatan Kearifan Lokal Berbantuan Flipbook pada Siswa Kelas VII MTs Negeri Padang Lawas Utara - Rezky Pandai Yani Tanjung; Syairal Fahmy Dalimunthe; Rosmawaty Rosmawaty; Safinatul Hasanah Harahap (Varied Knowledge Journal, 2026)
This study aims to develop teaching materials that integrate local wisdom using flipbooks, and to test their feasibility and effectiveness in Indonesian language classes focused on writing fantasy stories for seventh-grade students. This study is an R&D (Research and Development) study that uses the ADDIE model, evaluated by subject matter experts and design experts as validators, involving 26 seventh-grade students from MTs Negeri Padang Lawas Utara as the sample. The research results are as follows: (1) the development product is teaching materials developed with local wisdom using a flipbook, complete with content on writing fantasy stories, including structure, building elements, linguistic rules, and steps for writing fantasy stories; (2) the developed instructional materials were rated as highly suitable by the validators, with an 89% approval rate from subject matter experts and an 86% approval rate from design experts; and (3) the developed product proved effective when used in seventh-grade Class 1 instruction, with an average pretest score of 71 and a posttest score of 88. In general, it can be concluded that teaching materials incorporating local wisdom for writing fantasy stories have proven to be highly suitable and effective for use as supplementary teaching materials in fantasy story writing instruction, particularly for seventh-grade students at MTs Negeri Padang Lawas Utara.